The Influence of Mental Health in the Workplace on Employee Performance: Examining HR Policies as a Mediator - Kandel, Sudarshan (Devkota Journal of Interdisciplinary Studies, 2025)
This study investigates the influence of human resource (HR) policies and leadership support on workplace mental health and their subsequent effect on employee performance within the Nepalese banking sector. A structured questionnaire using a five-point Likert scale was administered to 404 banking professionals in the Rupandehi district of Nepal through convenience sampling. Structural Equation Modeling (SEM) was employed to examine the relationships among HR policies, workplace culture, job demands, leadership support, employee mental health, and performance. The SEM results demonstrate that supportive HR policies significantly enhance employee mental health (β = 0.42, p < .01), which in turn positively influences job performance (β = 0.38, p < .01). The overall model explains 52% of the variance in employee mental health (R² = .52) and 47% of the variance in performance outcomes (R² = .47). Supportive HR practices and a positive workplace culture reduce job stress and foster better work-life balance, thereby improving employee engagement and productivity Banking institutions should prioritize mental health initiatives through supportive HR policies and active leadership involvement to enhance employee well-being and performance. Such approaches may reduce healthcare expenses, lower turnover, and strengthen organizational competitiveness. This study contributes to the emerging literature on workplace mental health in Nepal’s banking sector by empirically validating the mediating role of HR policies and leadership support a dimension underexplored in previous Nepali research. It uniquely contextualizes the Job Demand Resource and Social Exchange theories within a South Asian banking environment, offering novel insights for scholars and practitioners.